2020
DOI: 10.1097/mpg.0000000000002563
|View full text |Cite
|
Sign up to set email alerts
|

Normal Gamma Glutamyl Transferase Levels at Presentation Predict Poor Outcome in Biliary Atresia

Abstract: Objectives: Gamma-glutamyl transferase levels (GGT) are typically elevated in biliary atresia (BA), but normal GGT levels have been observed. This cohort of “normal GGT” BA has neither been described nor has the prognostic value of GGT level on outcomes in BA. We aimed to describe outcomes of a single-centre Australian cohort of infants with BA and assess the impact of GGT level at presentation on outcomes in BA. Methods: Infants diagnosed with BA betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Previous studies have shown that a lower APRI at the time of KPE could predict a longer NLS [19,20], which is consisted with our findings. We also demonstrated that patients with low serum GGT levels prior to Kasai surgery were more likely to have poor prognosis, which was similar to that in several previous studies [15,16]. Studies [31,32] showed serum bilirubin level and ALB level could also influence NLS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have shown that a lower APRI at the time of KPE could predict a longer NLS [19,20], which is consisted with our findings. We also demonstrated that patients with low serum GGT levels prior to Kasai surgery were more likely to have poor prognosis, which was similar to that in several previous studies [15,16]. Studies [31,32] showed serum bilirubin level and ALB level could also influence NLS.…”
Section: Discussionsupporting
confidence: 89%
“…It has been shown that some preoperative parameters correlate well with the outcomes of KPE for BA infants. Studies have reported that a younger age was associated with a more favourable outcome [9][10][11][12][13][14], while low gamma-glutamyl transferase (GGT) level predicted a poor outcome in BA [15,16]. Other studies [11,[17][18][19][20] noted that the hepatic fibrosis stage and aspartate aminotransferase-to-platelet ratio (APRI) could be used to predict transplant-free survival time.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al found that the preoperative GGT level in BA patients who survived for >5 years with normal liver function was significantly higher than in those who died from liver failure within a year post- KP ( 25 ). Besides, Shankar et al retrospectively analyzed 113 BA patients and found that 12.3% of patients with preoperative GGT <200 IU/L experienced a shorter time from the KP to liver transplantation and poorer transplant-free survival than those with preoperative GGT > 200 IU/L ( 26 ). These results seemed to suggest that a low preoperative level of GGT may be associated with poor prognosis after KP.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a non-invasive and objective serum biomarker is clinically superior. Serum GGT levels were used to predict biliary atresia, however, its accuracy varied ( 19 , 20 ). Some studies also included GGT levels to develop a grading system (Grade I–III) for bile leakage severity in CC, with the serum GGT level for a Grade I diagnosis being 343.75 ± 215.6 U/L ( 6 ).…”
Section: Discussionmentioning
confidence: 99%